Energia solar fotovoltaica na matriz elétrica brasileira um estudo de caso em edificação pública - Martins, Eduardo Caldeira [UNIFESP] (2013)
This paper presents a study on the production of electricity from the sun for self-consumption in urban planning. The system that allows this conversion, named photovoltaic solar system, uses no batteries when connected to the electrical grid, what can substantially decrease its maintenance costs and initial investment regarding other photovoltaic solar energy systems. The goal of the paper involved checking the technical and financial feasibility of installing a solar plant to provide part of the electricity consumed at the José de Filippi Unit building of the Diadema Campus of the Federal University of São Paulo. A computer simulation was used in the adopted methodology, generating the optimization of the overall system performance among several types of equipment, installation angles and possible positioning. A payback study (return on investment) was also carried out taking into account the real costs of a bank financing for investments in this type of project, called the market "green line". The results showed that the proposed solar project has, in spite of a high initial cost, a payback of about 9.8 years, in an estimated system service life of over 20 years. It is a positive result both for the project itself and the environment, in that such projects reduce frequent losses in the transmission and distribution of electricity, common to the traditional system of centralized power generation adopted in Brazil today.